Implementasi Kebijakan Pendidikan (Budaya) Bela Negara: Studi Kasus SD Katolik Karya Toboali, Kepulauan Bangka Belitung - Fatkhuri Fatkhuri (Inovasi, 2021)
This study aims to grasp the policy of state defense which embedded through the form of school culture which plays an important role to shape the character of state defense in Katolik Karya, Toboali Elementary School, Bangka Belitung. This also seeks to capture how state defense culture is effectivelly implemented to support the students’ character. This study uses descriptive qualitative, in which data and information are obtained through interviews, questionnaires, and documents involving principals, teachers, education staff, and students. This study found that the school already has developed policy to instill a state defense culture which is introduced by the Tunas Karya Foundation. The state defense policy is developed through a set of values which are arranged in the ten main character as a genuine of cultural product to form of student character. Schools conduct a state defense policy through habituation with a nurturing and modeling approach by teachers. This study also shows that the habituation of the ten main character values in making state defense behavior is quite effective. Based on the assessment results, the data shows that the majority of students have regularly employed the habituation of the state defense with average marks at 82 point.